MERLEAU-PONTY ENTRE O SENSÍVEL E A NATUREZA: CONSIDERAÇÕES A RESPEITO DA SUA ÚLTIMA ONTOLOGIA (Phenomenology, Humanities and Sciences, 2025)
In the posthumous writings that form the “Visible and the Invisible”, Merleau-Ponty is adamant about the problematic of the conception of the being-subject, stating that, just like the conception of the being-object, it does not constitute an alternative, as the perceived world falls short or beyond antinomy. Therefore, it is urgent to review our ontology. In this article, we will present a diagnosis of the analysis of the sensible world and the natural world in Merleau-Ponty’s last ontology. The purpose is to explain, above all, how it grounds the rehabilitation of the idea of sensible and nature for the description of flesh. We will see the consequences of the foundation of the ontology of brute being in the light of commentators, its difficulties, its scope and structure, and, consequently, the importance of its elaboration for philosophy and contemporary phenomenology as an opening to the world.
Keywords: Phenomenology; Merleau-Ponty; Nature; Ontology; Sensible